The Impact of Financial Literacy and the Ease of Digital Technology on the Income of MSMEs in Makassar City - Nurjannah, Nurjannah; Sitti Hajerah Hasyim (Cita konsultindo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a business sector that plays a vital role in the national economy. MSMEs are the backbone of a country's economy during an economic crisis. The purpose of this study is to examine the effect of digital technology and financial literacy on MSME income in Mamajang District, Makassar City. This study employed purposive sampling and quantitative methodology, with 100 respondents as a sample. Data collection methods used were direct observation and questionnaire distribution. Data analysis used Smart PLS software. The results show that digital technology and financial literacy are important factors in increasing MSME income. Therefore, MSMEs are expected to continue to improve their understanding of financial literacy and optimize the use of digital technology to support the success and sustainability of their businesses.